Adult linear IgA bullous dermatosis: report of three cases - Taila Yuri Siqueira Machado; Milvia Maria Simões e Silva Enokihara; Tatiana Miyuki Iida; Adriana Maria Porro (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Linear immunoglobulin A bullous dermatosis is a rare autoimmune disease that usually has an excellent prognosis in childhood; however, its control is more difficult in adults. It presents heterogeneous clinical manifestations and is frequently confused with other bullous diseases such as bullous pemphigoid and Duhring's dermatitis herpetiformis. Dermatologists' awareness of this disease contributes to early diagnosis and appropriate treatment. We thus report three cases of linear immunoglobulin A dermatosis in adults.